Headbobber: a combined morphogenetic and cochleosaccular mouse model to study 10qter deletions in human deafness. - Annalisa Buniello; Rachel E Hardisty-Hughes; Johanna C Pass; Eva Bober; Richard J Smith; Karen P Steel (PLoS ONE)
The recessive mouse mutant headbobber (hb) displays the characteristic behavioural traits associated with vestibular defects including headbobbing, circling and deafness. This mutation was caused by the insertion of a transgene into distal chromosome 7 affecting expression of native genes. We show that the inner ear of hb/hb mutants lacks semicircular canals and cristae, and the saccule and utricle are fused together in a single utriculosaccular sac. Moreover, we detect severe abnormalities of the cochlear sensory hair cells, the stria vascularis looks severely disorganised, Reissner's membrane is collapsed and no endocochlear potential is detected. Myo7a and Kcnj10 expression analysis show a lack of the melanocyte-like intermediate cells in hb/hb stria vascularis, which can explain the absence of endocochlear potential. We use Trp2 as a marker of melanoblasts migrating from the neural crest at E12.5 and show that they do not interdigitate into the developing strial epithelium, associated with abnormal persistence of the basal lamina in the hb/hb cochlea. We perform array CGH, deep sequencing as well as an extensive expression analysis of candidate genes in the headbobber region of hb/hb and littermate controls, and conclude that the headbobber phenotype is caused by: 1) effect of a 648 kb deletion on distal Chr7, resulting in the loss of three protein coding genes (Gpr26, Cpmx2 and Chst15) with expression in the inner ear but unknown function; and 2) indirect, long range effect of the deletion on the expression of neighboring genes on Chr7, associated with downregulation of Hmx3, Hmx2 and Nkx1.2 homeobox transcription factors. Interestingly, deletions of the orthologous region in humans, affecting the same genes, have been reported in nineteen patients with common features including sensorineural hearing loss and vestibular problems. Therefore, we propose that headbobber is a useful model to gain insight into the mechanisms underlying deafness in human 10qter deletion syndrome.